Competencies for effective leadership : a framework for assessment, education, and research - Gigliotti, Ralph A. (Bingley, U.K. : Emerald Publishing Limited, 2019)
What makes a leader? In this critical time of change for leaders, it has become increasingly important to understand the competencies associated with leadership. This essential book explores the ways in which Brent Ruben's Leadership Competency Scorecard can be used within an organizational setting.
Prelims -- An Introduction to competencies and competency-based leadership -- An introduction to the leadership competency framework -- Snapshot of leadership education connections -- Contributions of the leadership competency framework to leadership research -- Appendix -- Index.
Includes index.
Print version record
Keywords: Leadership; Business & Economics -- Leadership; Management: leadership & motivation